Home >> Standard Identities & their applications >>

Standard Identities & their applications

(a + b)2 = a2 + b2 + 2ab (a - b)2 = a2 + b2 - 2ab a2 - b2 = (a + b) (a - b) (x + a) (x + b) = x2 + x(a + b) + ab (a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca (a + b)3 = a3 + b3 + 3ab(a + b) (a - b)3 = a3 - b3 - 3ab(a - b) a3 + b3 + c3 - 3abc = (a + b + c)(a2 + b2 + c2 - ab - bc - ca)

Here you can study the following algebraic identities:

Identity I = (a + b)2 = a2 + b2 + 2ab

Identity II = (a + b)2 = a2 + b2 - 2ab

Identity III = a2 - b2 = (a + b) (a - b)

Identity IV = (x + a) (x + b) = x2 + (a + b)x + ab

Identity V = a + b + c)2 = a2 + b2 + c2 + 2ab + 2bc + 2ca

Identity VI = (a + b)3 = a3 + b3 + 3ab(a + b)

How these identities are obtained and Application of these identities can be study from the above provided respective links:


  ×